Family experiences of personalised accommodation and support for people with intellectual disability - Garcia Iriarte, Edurne (My University, 2020)
Previous studies suggest that family members of people with intellectual disabilities prefer them to move to supervised living arrangements such as group homes. In Ireland, personalised arrangements are emerging, but families have had little exposure to this option. In this qualitative study, we explored the perspectives of family members following their relative’s move to personalised support options, mostly from group homes. Semi-structured interviews were conducted in 2011 with a family member of 17 people who had previously moved, with follow-up interviews held with 12 of them up to 18 months later. Thematic analysis on interview transcripts was conducted by three researchers. The family members spoke favourably of the new arrangements. A core theme of enabled independence emerged with subthemes of greater self-reliance in personal care, increased confidence, more social inclusion and gains for relatives. Reservations focussed on the need for more support hours, managing risk and loneliness.
PUBLISHED
Keywords: Intellectual disability; Community living; Family; Ireland; Personalised accommodation; Inclusive Society; Community living; FAMILY; INTELLECTUAL DISABILITY; IRELAND; Personalised accommodation